Mídia, memória pública e comissão da verdade no Brasil: a luta pela verdade e justiça como uma luta por reconhecimento - Vanessa Veiga de Oliveira (2017)
The thesis defended in this work is that the struggle for truth and justice in Brazil is a struggle for recognition. To do so, we articulate the concepts of struggle for recognition (HONNETH, 2003) and public memory (JELIN, 2002) based on the analysis of the personal histories that circulated about the civil-military dictatorship during the National Truth Commission (2012-2014). We analyzed the semantic constructions, that is, the collective and shared interpretations about the history of the dictatorship. These interpretations were found in the following arenas: (1) in the testimonies of the public hearings conducted by the National Truth Commission (NTC); (2) on NTCs Facebook posts; (3) in the news circulated in two national newspapers (O Estado de São Paulo and Folha de São Paulo). We are interested in identify who is the actor of the speech act; who is the subject of talk and what their claims of recognition are about. The analysis pointed out the existence of the circulation of the semantics of the struggle along the three arenas, but with its own characteristics. While newspapers centered their coverage on the clarification of military's actions, the Commission's official Facebook page sought to give more visibility to family members, revealing a race for perspective in building public memory. Our findings also reveal a protagonist of the military as subjects and objects of the acts of speech analyzed. This finding reveals the difficulty of deepening the notion of who were victims of the military regime and of drawing an approach to these victims and their histories. In addition, the dissertation stresses the theory of recognition regarding the possibility of self-actualization of the subjects. We conclude that the struggle for recognition continues in the country, but it was crossed by the structural issues that constitute the work of memory in the country and by the dichotomy imposed in a public debate marked by a deep division.